Parallel multi-stacked photoanodes of Sb-doped p–n homojunction hematite with near-theoretical solar conversion efficiency - Chenyang Xu; Hongxin Wang; Hongying Guo; Ke Liang; Yuanming Zhang; Weicong Li; Junze Chen; Jae Sung Lee; Hemin Zhang (Nature Communications)
Abstract Developing transparent and efficient photoanodes is a challenging but essential task in tandem photoelectrochemical cell for unassisted solar water splitting without an external bias. Here we report construction of p–n homojunction hematite photoanodes by hybrid microwave annealing-induced single antimony doping, which results in the gradually-increased valence states from the surface to the inside by the unique features of hybrid microwave annealing. The Sb-doped p–n homojunction hematite photoanode exhibits improved performance and displays a good transparency, achieving a stable photocurrent density of ~4.21 mA cm−2 at 1.23 VRHE under 100 mW cm−2 solar irradiation, which is comparable to the reported state-of-the-art hematite photoanodes. More importantly, a parallel-connected stack of six photoanodes of transparent p–n homojunction records a near-theoretical photocurrent density of ~10 mA cm–2 at 1.23 VRHE under standard photoelectrochemical water splitting conditions, which serves as a useful reference for hematite photoanodes and promises its practical application for unbiased photoelectrochemical water splitting.